Urban expansion and reduction of green areas in Salvador/BA: the case of São Bartolomeu Park (Research, Society and Development, 2020)
The urban fabric of cities appears as a result of the processes of interaction between individuals and the natural environment, in this sense, theoretically, the aspect of urbanization tends to reflect the progress and development of society. However, social segregation, environmental degradation and lack of services and infrastructure make up the common problems of almost all major Brazilian cities. The purpose of this article is to analyze how the city's expansion process directly impacts the degradation of São Bartomoleu Park, located in the Suburbio Ferroviário de Salvador, Bahia. The methodology adopted in this article covers the bibliographic review on the subject and, thus, the results obtained confirm that the disorderly occupation allows the reduction of free green areas and of quality of urban life.